PENYELESAIAN KREDIT MACET PT. BPR ARTO MORO SEMARANG MELALUI EKSEKUSI HAK TANGGUNGAN - Fandil, Fandil; Fitika Andraini (Jurnal Ilmiah Dinamika Hukum, 2021)
The provision of credit / loans by credit-giving institutions, both banks and other financial institutions, is intended as an effort to make a profit, so the lending institution views credit / loans as a reliable source of income or profit. In connection with the issue of credit / loan provision, credit institutions such as PT. BPR Arto Moro Semarang as the party that lends money (creditors) needs to get a guarantee as a condition for the loan that the debtor will receive on condition that he gives interest when repaying the loan. In practice, the obstacles that PT. BPR Arto Moro Semarang, especially for debtors with guarantees by using the Deed of Providing Mortgage Rights (APHT) which is registered with the National Land Agency (BPN), if the credit is jammed and failed to promise, the bank will take the final step in accordance with applicable law, namely implementing execution of mortgage rights through the Office of State Wealth and Auction Services (KPKNL) or through the District Court (PN). The type of research used in this research is normative juridical. Juridical research, is used, among other things, to analyze various legal theories and laws and regulations related to the juridical review of the accounts payable agreement as a principal agreement with guarantees of insurance rights at PT. BPR Arto Moro Semarang. Juridical means that this research emphasizes the science of law. Meanwhile, normative is this research that examines the rules that apply in society. Thus normative juridical is an approach to the study of legal problems from the aspect of applicable legal regulations. The results of this study are: the settlement of bad credit tied to mortgage rights at PT. BPR Arto Moro Semarang after performing credit rescue through 3R (rechedulling, restructuring and reconditioning). Before the execution of mortgage rights is carried out, non-litigation measures by way of selling collateral based on mutual agreement based on paragraph (2) article 20 of the Mortgage Rights Law. During 2018 to 2020 Mortgage Execution can contribute to the settlement of non-performing loans as much as 45% or Rp. 15,731,212,000, - from an amount of Rp. 34,964,970,686, -. Meanwhile, the occurrence of bad credit is due to internal factors: a. Loans not fully channeled for business, b. Business management skills are still lacking, c. Very tight business competition. External factors are due to unstable economic conditions, which consequently have an impact on the ability of customers to pay off their debts. Keywords : Bad credit, collateral, execution, and mortgage.